2012
DOI: 10.1016/j.fertnstert.2012.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Changes in use of long-acting contraceptive methods in the United States, 2007–2009

Abstract: Objectives To examine trends in use of long-acting reversible contraceptive (LARC) methods — the IUD and implant — and the extent to which these methods have replaced permanent sterilization and less-effective short-acting methods. Design We tabulated data from female survey respondents overall and by demographic subgroups. We performed t-tests of the differences in the proportions of female contraceptors using LARC in 2007 and 2009. We also looked at use of LARC, sterilization, other methods and no method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
219
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(229 citation statements)
references
References 11 publications
7
219
2
1
Order By: Relevance
“…Women choosing an IUD for contraception have the highest continuation and satisfaction rates compared to other contraceptive methods [26]. In recent years, IUD use has risen predominately among parous women [27], and as our study confirmed low pain levels with IUD insertion among parous women, likely no additional pain intervention is necessary for this group. However, reducing pain with IUD insertion among nulliparous women may increase the acceptability of this highly effective contraceptive method for this group.…”
Section: Discussionsupporting
confidence: 60%
“…Women choosing an IUD for contraception have the highest continuation and satisfaction rates compared to other contraceptive methods [26]. In recent years, IUD use has risen predominately among parous women [27], and as our study confirmed low pain levels with IUD insertion among parous women, likely no additional pain intervention is necessary for this group. However, reducing pain with IUD insertion among nulliparous women may increase the acceptability of this highly effective contraceptive method for this group.…”
Section: Discussionsupporting
confidence: 60%
“…contracepting women using IUDs increasing from 3.7% in 2007 to 8.5% in 2009 (Finer, Jerman, & Kavanaugh, 2012) While training providers and the amelioration of co-pay requirements should make IUDs accessible for many women, there are additional reasons why IUD uptake may remain low.…”
Section: Introductionmentioning
confidence: 99%
“…Women younger than 30 years at the time of sterilisation report especially high levels of post-sterilisation regret and are almost twice as likely to report regret as those older than 30 years [13]. Age less than 30 years was the strongest risk factor in an Indian study [14].…”
Section: Larc As An Alternative To Sterilisationmentioning
confidence: 99%